2023
DOI: 10.1002/sae2.12055
|View full text |Cite
|
Sign up to set email alerts
|

Predicting soil fungal communities from chemical and physical properties

Natacha Bodenhausen,
Julia Hess,
Alain Valzano
et al.

Abstract: IntroductionBiogeography describes spatial patterns of diversity and explains why organisms occur in given conditions. While it is well established that the diversity of soil microbes is largely controlled by edaphic environmental variables, microbiome community prediction from soil properties has received less attention. In this study, we specifically investigated whether it is possible to predict the composition of soil fungal communities based on physicochemical soil data using multivariate ordination.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Van Aarle et al 2002). Soil pH can drive mycorrhizal fungal community composition (Hazard et al 2013;Davison et al 2021;Bodenhausen et al 2023) and can affect AM fungal communities and plant growth directly by modifying enzymatic activities or indirectly by affecting soil nutrient availability (Haynes 1990;Marschner 1995). Our results at Steptoe Butte are consistent with studies showing that some invasive plant species (e.g.…”
Section: Soil Ph and Om Were Higher In Invaded Plotssupporting
confidence: 88%
“…Van Aarle et al 2002). Soil pH can drive mycorrhizal fungal community composition (Hazard et al 2013;Davison et al 2021;Bodenhausen et al 2023) and can affect AM fungal communities and plant growth directly by modifying enzymatic activities or indirectly by affecting soil nutrient availability (Haynes 1990;Marschner 1995). Our results at Steptoe Butte are consistent with studies showing that some invasive plant species (e.g.…”
Section: Soil Ph and Om Were Higher In Invaded Plotssupporting
confidence: 88%
“…Different soil types were examined in ref. 28 . We first assessed pairwise correlations between soil properties and MGR for 54 fields.…”
Section: Resultsmentioning
confidence: 99%
“…We determined the soil fungal communities with long-read sequencing and found a high relative abundance of Ascomycota, followed by Mortierellomycota and Basidiomycota 28 (Supplementary Table 6 ). Rarefaction analysis confirmed that sufficient sequencing depth was reached to capture the fungal diversity 28 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Soil attributes, encompassing pH, texture, nutrient availability, and organic matter content, profoundly in uence microbial communities, fungi included. The spatial distribution of fungal populations within soil intricately intertwines with these physicochemical attributes, delineating the heterogeneous nature of soil habitats and the diverse ecological niches they offer (Canini et al, 2019;Trivedi et al, 2020;Bodenhausen et al, 2023).…”
Section: Introductionmentioning
confidence: 99%